South Korea’s Economic Cooperation with Russia and North Korea in the Arctic: Challenges and Recommendations - Yeonji Ghim 1992- (2021)
This paper takes a novel approach to analyzing South Korea’s Arctic policy from the context of South Korea’s inter-Korean security goal of inducing North Korea to denuclearize and adopt an economic reform. South Korea's second Arctic master plan published in 2018 emphasizes the strategic direction of expanding economic cooperation with Russia in the Arctic. This paper argues that South Korea’s Russia-Centric Arctic economic policy has a strong inter-Korean policy orientation, and points to two major geopolitical factors that stall Seoul’s partnership with Moscow in the Arctic: First, South Korea’s interest in promoting inter-Korean cooperation in the Arctic that supersedes its interest in cooperating with Russia; Second, South Korea’s cooperation with Russia as well as North Korea in the Arctic poses security threats to the US, which is South Koreas closest ally and the world’s hegemonic power. Based on analysis of challenges that face South Korea’s current Arctic economic strategy, the paper recommends policy directions to help South Korea more efficiently pursue its economic and political interests in the Arctic.